Participating with a Real Name, a Nickname or by Being Anonymous? – Anonymous and Identifiable Users' Skills and Internet Usage Habits - Meri-Tuulia Kaarakainen; Heikki Hutri (Tampereen Yliopisto, 2022)
Data consisting of Finnish youths' technology usage habits and ICT skill test results are analysed in this paper. The analysis focuses especially on young people's preferences in presenting themselves online: whether they act under their real name, with pseudonym, anonymously or with some combination of these, and whether or not these choices relate with the respondents’ information security skills in particular and ICT skills in general. The analysed data includes responses from 3,184 youths aged between 12 and 23 years. The results show that the most preferred way to be online is under a pseudonym followed by those using their legal names, while only less than one out of ten chose to use the Internet anonymously. Girls use their legal names significantly more often than boys, while boys in their turn are pseudonymous users more often than girls. Pseudonymous users were the most competent in the ICT skill test in general and also in all three information security sub-areas. Pseudonymous use was also found to correlate with more extensive use of Internet services and digital technologies than those using their legal name or being anonymous.
Tuovi 14: Interaktiivinen tekniikka koulutuksessa 2016-konferenssin tutkijatapaamisen artikkelit